A wide range of pheromone-stimulated sexual and reproductive behaviors in female mice depend on G protein Gαo - Oboti, Livio (2014)
Optimal reproductive fitness is essential for the biological success and survival of species. The vomeronasal organ is strongly implicated in the display of sexual and reproductive behaviors in female mice, yet the roles that apical and basal vomeronasal neuron populations play in controlling these gender-specific behaviors remain largely unclear. Results To dissect the neural pathways underlying these functions, we genetically inactivated the basal vomeronasal organ layer using conditional, cell-specific ablation of the G protein Gαo. Female mice mutant for Gαo show severe alterations in sexual and reproductive behaviors, timing of puberty onset, and estrous cycle. These mutant mice are insensitive to reproductive facilitation stimulated by male pheromones that accelerate puberty and induce ovulation. Gαo-mutant females exhibit a striking reduction in sexual receptivity or lordosis behavior to males, but gender discrimination seems to be intact. These mice also show a loss in male scent preference, which requires a learned association for volatile olfactory signals with other nonvolatile ownership signals that are contained in the high molecular weight fraction of male urine. Thus, Gαo impacts on both instinctive and learned social responses to pheromones. Conclusions These results highlight that sensory neurons of the Gαo-expressing vomeronasal subsystem, together with the receptors they express and the molecular cues they detect, control a wide range of fundamental mating and reproductive behaviors in female mice.